Sellaphora jiuzhaienis sp. nov. (Bacillariophyceae)—A new diatom species from Jiuzhaigou National Nature Reserve, China - SUN, GENG; LEVKOV, ZLATKO; XIAO, WEIYANG; MORAJ, NIKOLA; UDOVIČ, MARIJA GLIGORA; DU, JIE; CHEN, QUNLONG; PLENKOVIĆ-MORAJ, ANĐELKA (Magnolia Press, 2023)
A new species Sellaphora jiuzhaienis sp. nov. was found in epilithic samples from Jiuzhaigou National Nature Reserve, China. The species is described herein as new to science based on light microscopy (LM) and scanning electron microscopy (SEM), and ecological information is provided. The species has linear to linear-elliptic valves, 17.5–33.5 μm long and 7.0–8.5 μm wide and very broad conopeum that occupies almost half of the valve width. The discovery of a new diatom species confirms the importance of Jiuzhaigou not only in terms of species richness and endemicity but also for the biodiversity of freshwater karst ecosystems in the national protected areas of China.